The HARDNESS POLYURETHANE AND NATURAL RUBBER EFFECT ON ADHESIVENESS OF AIRLESS TIRES - Annas, Assyifa; Saefullah, Lalu; Hidayat, Muhammad Iman (Pustaka Poltekad, 2021)
Abstract: Airless tires are the best innovation for military tactical vehicles in carrying out the Army's main tasks for military tactical even peace support operations and war military operations. However, in its development there are still imperfections in the results, its fabrications in the adhesion between polyurethane and natural rubber. Therefore, the researchers aimed to develop the adhesion between polyurethane and natural rubber. In this research, a quantitative experimental method was used, namely by varying the hardness of natural rubber and polyurethane to determine the right hardness for airless tires for maximum adhesion. The problem that occurs is that the adhesive glue with the tire tread is problematic, resulting in a tire tread condition without air being released. In carrying out the research, a function test was carried out with a planned weight of 4,500 Kg. Based on the results of the tests that carried out, the correct result was obtained, namely the elongation at break of the most appropriate type of polyurethane L100, which was 9.287 MPa. In order to achieve the goal, namely the appropriate level of elasticity between polyurethane and natural rubber so as to be able to glue the spokes and tire treads, in the end the wheel rotation will rotate according to the desired elasticity.